1991
DOI: 10.1128/iai.59.11.4249-4251.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of murine monoclonal antibodies that recognize defined epitopes of pertussis toxin and neutralize its toxic effect on Chinese hamster ovary cells

Abstract: Three murine monoclonal antibodies (MAb), E19, E205, and E251, raised against pertussis toxin reacted in Western blots (immunoblots) with the Si, S4, and S2-S3 subunits, respectively, and neutralized the Chinese hamster ovary cell-clustering activity of pertussis toxin. MAb E251 recognized a linear synthetic peptide corresponding to amino acids 107 to 120 of the S2 subunit, suggesting a role for this region in receptor binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Antibodies directed against various $2-or S3-specific peptides showed that those reacting with peptides corresponding to the regions located in the vicinity of residue 105 have the highest toxin-neutralizing activities, presumably because of their interaction with receptor binding (40). On the other hand, most toxin-neutralizing mAbs reactive with the B oligomer, including those presented in this study, appear to recognize conformational epitopes (41,42), suggesting that the receptor-binding of PTX depends on the conformation of the B oligomer.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies directed against various $2-or S3-specific peptides showed that those reacting with peptides corresponding to the regions located in the vicinity of residue 105 have the highest toxin-neutralizing activities, presumably because of their interaction with receptor binding (40). On the other hand, most toxin-neutralizing mAbs reactive with the B oligomer, including those presented in this study, appear to recognize conformational epitopes (41,42), suggesting that the receptor-binding of PTX depends on the conformation of the B oligomer.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were heated at 95ЊC for 5 min, and after centrifugation (1 min at 17000 ϫ g), 10 l of each supernatant was spotted onto nitrocellulose membranes (Bio-Rad Laboratories, Munich, Germany). The membranes were blocked for 1 h with 10% low-fat milk (0.3%) in PBS and further incubated for 2 h with a cocktail of appropriately diluted monoclonal antibodies E19, E205, and E251 (38), which are reactive with PT subunits. The proteins were detected by using antibody peroxidase-conjugated goat anti-mouse immunoglobulin G as a secondary antibody (Bio-Rad Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…For immunoelectron microscopy, uncoated or antigencoated liposomes were absorbed onto freshly prepared collodium-covered 300-mesh nickel grids and carefully washed with distilled water. After being air dried at room temperature, the grids were treated with protein A-purified anti-FHA or anti-PT polyclonal (21,50) or monoclonal (14,51) antibodies (125 jig of IgG protein ml-') for 60 min at room temperature. Unbound antibodies were removed by a mild spray of PBS (pH 6.9) from a plastic bottle.…”
Section: Methodsmentioning
confidence: 99%